The Effect of Firm Location on Corporate Dividend Policy: Study in Indonesia Capital Market - Hakim, Muhammad Saiful; Liu, Chih Liang (University of Merdeka Malang, 2023)
This research explored the effect of firm location in Indonesia on corporate dividend policy. The location variable in this research was represented by firm location in Jakarta, which is the capital city of the state, and firm location on Java, where three largest cities in Indonesia are situated. The empirical results of this research indicated that firms that are situated on Java Island had a tendency to have lower payout ratios than their counterparts off the island. Meanwhile, there were no empirical proofs showing that firms in Jakarta had different payout ratios. This depicts that firms that are situated beyond a financial hub have the drive to pay more dividends to their shareholders, signaling the presence of greater information asymmetry for such firms. The result still consistent after considering several robustness tests include, using alternative proxy for dividend policy, exclude crisis period and exclude upper and lower group in research sample.DOI: 10.26905/jkdp.v27i1.9355